2013
DOI: 10.15395/mkb.v45n4.170
|View full text |Cite
|
Sign up to set email alerts
|

Validitas Metode Polymerase Chain Reaction GeneXpert MTB/RIF pada Bahan Pemeriksaan Sputum untuk Mendiagnosis Multidrug Resistant Tuberculosis

Abstract: AbstrakPengendalian tuberkulosis saat ini terkendala oleh metode diagnostik konvensional yang lambat terutama untuk mendeteksi multidrug resistant tuberculosis (MDR-TB). Deteksi dini MDR-TB sangat penting untuk mencegah penyebaran MDR-TB dan mengurangi angka kematian. Validity of Polymerase Chain Reaction GeneXpert MTB/RIF Method on Sputum Sample Examination to Diagnose Multidrug Resistant Tuberculosis AbstractControl of tuberculosis is hampered by slow conventional diagnostic methods especially for the detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…Another study conducted by Sirait et al also showed that the most common complaint (88%) was chronic cough. 18 Other symptoms that might be present are shortness of breath, chest pain, bloody cough or hemoptysis, and systemic symptoms i.e., fever, chills, night sweats, fatigue or malaise, and weight loss. 19 About 71.8% of subjects in this study had positive AFB smear result (scanty, 1+, 2+, 3+).…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted by Sirait et al also showed that the most common complaint (88%) was chronic cough. 18 Other symptoms that might be present are shortness of breath, chest pain, bloody cough or hemoptysis, and systemic symptoms i.e., fever, chills, night sweats, fatigue or malaise, and weight loss. 19 About 71.8% of subjects in this study had positive AFB smear result (scanty, 1+, 2+, 3+).…”
Section: Discussionmentioning
confidence: 99%
“…As the results of research conducted by Sirait et al which states that molecular rapid test kits are suggested as the primary screening tool for MDR-TB. 15 Likewise with research that has been done by Cox et al, Gomez et al, Saeed et al and Evan et al which all state that the enforcement of MDR-TB diagnoses should have used the rapid examination method. 16,17,18,19 The rapid test can work in as little as 2 hours as stated in the research of Saeed et al 19 The results of examinations that we're able to be carried out briefly were found no significant differences when compared with the results of examinations conducted by microscopy or culture methods, as stated by Lebina et al in his research.…”
Section: "The Lack Of Repairs and Improvements To Some Unrepresentative Building Facilities Including Mdr-tb Inpatient Wards Whose Treatmmentioning
confidence: 94%
“…Beberapa penelitian telah mengungkapkan tambahan zat untuk meningkatkan haemoglobin yang dengan mudah ditemukan serta mengolahnya, berasal dari tanaman lokal yaitu daun kelor (Moringa oleifera). Study yang dilakukan secara in vivo, ternyata daun kelor juga dapat meningkatkan berat badan anak serta jumlah sel darah merah (5) . Peneliti lain juga mengungkapkan bahwa pemberian ekstrak biji klabet dan daun kelor dapat meningkatkan jumlah produksi air susu ibu sehingga berat badan anak meningkat, hal ini dapat digunakan sebagai pencegahan terjadinya stunting (6) (7) .…”
Section: Pendahuluanunclassified